The transforming proteins of PRCII virus and Rous sarcoma virus form a complex with the same two cellular phosphoproteins. - Adkins, B (1982)
P105 and P110, the presumptive transforming proteins of PRCII avian sarcoma virus, have been found to be present in transformed chicken cells in two forms: as monomers and as part of a complex which contains both a 50,000-dalton and a 90,000-dalton cellular phosphoprotein. The 90,000-dalton cellular protein was found to be identical to one of the proteins in chicken cells whose synthesis is induced by stress. The 50,000-dalton protein was found to contain phosphotyrosine when isolated from the complex and therefore may be a substrate for the tyrosine protein kinase activity which is associated with P105 and P110. These same two cellular phosphoproteins have previously been shown to be present in a complex with pp60src, the tyrosine protein kinase which is the transforming protein of Rous sarcoma virus. However, not all avian sarcoma virus transforming proteins with associated tyrosine protein kinase activities form a complex efficiently with these cellular proteins. Little if any of P90, the putative transforming protein of Yamaguchi 73 virus, was found in a complex with the 50,000-dalton and 90,000-dalton cellular phosphoproteins.